On the Upper Mid-Band 8 × 8 and 8 × 4 Device MIMO Performance Based on Applying Compact Backcover Four-Antenna Modules for 6G Smartphones With Increased Data Rates - Kin-Lu Wong; Wan-Ting Li; Chin-Lung Wang; Chun-Chi Wen; Wei-Yu Li (IEEE Access)
For future six-generation (6G) upper mid-band mobile communications, the higher-order device multi-input-multi-output (MIMO) such as the $8× 8$ or $8× 4$ MIMO is envisioned for the smartphone to achieve increased data rates for the user. However, it is worth noting that the $8× 8$ MIMO requires twice the transmitted power of current fifth-generation (5G) $4× 4$ MIMO and has a much more complex system architecture. Thus, whether it is cost effective to apply the $8× 8$ MIMO for increased data rates is not clear. In this study, we demonstrate that the $8× 4$ MIMO (8 receive antennas for 4 spatial streams) with the same transmitted power as the 5G $4× 4$ MIMO can outperform the $8× 8$ MIMO to achieve increased data rates and lower energy per bit as well. In the outdoor scenario testing, the $8× 4$ MIMO shows a spectral efficiency of about 31 or 26 bps/Hz, while that of the $8× 8$ MIMO is only about 22 bps/Hz. Additionally, the required energy per bit transmitted in the $8× 4$ MIMO is less than one-half that of the $8× 8$ MIMO. The is mainly because the $8× 4$ MIMO uses only one-half transmitted power and has a much larger MIMO efficiency (measured system capacity/ideal system capacity) than the $8× 8$ MIMO. Thus, the $8× 4$ MIMO can support a higher signal modulation of 256 or 1024 Quadrature Amplitude Modulation (QAM), while the $8× 8$ MIMO supports only 16 QAM. Hence, although the $8× 8$ MIMO has a potentially much larger system channel capacity, its actual data throughput cannot be proportionally larger. We experimentally evaluate the MIMO performance in the 7.1 GHz band by applying compact backcover four-antenna (B4A) modules as receive antennas in the smartphone-like device covering 6.425-8.4 GHz in the upper mid-band, which is promising to be a prime 6G mobile spectrum. The applied compact B4A module provides a promising solution for the challenge in embedding at least 8 MIMO antennas in 6G smartphones for upper mid-band MIMO communications. We present details of the $8× 8$ and $8× 4$ MIMO performance testing and the applied B4A modules for promising 6G smartphone applications.